Ribosomal DNA internal transcribed spacer analysis supports synonomy of Scedosporium inflatum and Lomentospora prolificans. - Lennon, P A (1994)
Scedosporium inflatum is a dematiaceous opportunistic pathogen originally described by D. Malloch and I.F. Salkin (Mycotaxon 21:247-255, 1984). However, E. Gueho and G. S. De Hoog (J. Mycol. Med. 118:3-9, 1991) recently suggested reducing this mold to synonomy with Lomentospora prolificans on the basis of their similar morphological and molecular characteristics. We have investigated the ribosomal DNA internal transcribed spacers (ITS), i.e., ITS I and ITS II, of 18 isolates, including these two fungi and a closely related pathogen, Scedosporium apiospermum, and its telemorph, Pseudallescheria boydii. Identical ITS restriction fragment length polymorphisms were found in eight isolates of S. inflatum and L. prolificans. These results support Gueho and De Hoog's proposal to combine S. inflatum and L. prolificans into the binomial Scedosporium prolificans. However, the ITS I sequence of S. apiospermum and the ITS restriction fragment length polymorphisms of S. apiospermum and P. boydii were found to be significantly different from those of S. inflatum and L. prolificans. The ITS restriction pattern differences may be valuable in clinical settings for distinguishing these fungi.